2007
DOI: 10.1097/wnr.0b013e32802b70e2
|View full text |Cite
|
Sign up to set email alerts
|

Localization of hyaluronan in the optic pathway of mouse embryos

Abstract: CD44 has been shown to be involved in midline crossing and the generation of ipsilateral projections in the mouse optic chiasm. To determine whether these functions involve hyaluronan, the major ligand of CD44, we examined localization of hyaluronan in the mouse optic pathway. Hyaluronan was deposited mainly in vitreal regions of the retina and the optic disk. In ventral diencephalon, it was localized largely on the chiasmatic neurons that project processes to the chiasmatic midline and the optic tract. Coloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Neural and glial cells synthesize HA in culture and as an ECM CNS component (Lin et al . ; Meszar et al . ; Hagenfeld et al .…”
Section: Kspgs Of the Cns/pnsmentioning
confidence: 99%
“…Neural and glial cells synthesize HA in culture and as an ECM CNS component (Lin et al . ; Meszar et al . ; Hagenfeld et al .…”
Section: Kspgs Of the Cns/pnsmentioning
confidence: 99%
“…Another region that HA serves as a guidance molecule is the optic chiasm, where those axons of the optic nerve coming from the nasal halves of retina will cross and give rise to the very specific optic pathway. HA localizes in the medial part of the optic chiasm, the point where axon crossing takes place 65 . Data suggests the HA receptor CD44 is involved in mediating the HA role in axon crossing.…”
Section: Hyaluronan and Axon Growthmentioning
confidence: 95%
“…These proteoglycans include sulphated molecules chondroitin sulphate proteoglycans (CS-PGs) and heparan sulfate proteoglycans (HS-PGs), a type of nonsulfated linear glycosaminoglycan hyaluronan (HA), and the cell surface carbohydrate molecule SSEA-1, which is also known as CD15 (leukocyte cluster of differentiation 15) and Lewis-x, a member of the Lewis blood group antigens in humans [24]. By immunohistochemisty using antibodies specific for different glycan epitopes and antibodies against carrier proteins of glycans, they observed specific expression of each of these proteoglycans along the retinofugal pathway [11,13,14,17,19,20,22]. They found that cell adhesion molecules that may recognize these proteoglycans [25,26], including L1, the poly-sialylated form of NCAM (PSA-NCAM) and CD44, are also expressed in a site-specific pattern along the optic pathway at comparable developmental stages [15,16], consistent with the previous reports [27,28].…”
Section: Guidance Of Retinal Axons In the Optic Chiasm By Proteoglycansmentioning
confidence: 97%
“…The potential contributions of glycan molecules present in developing brain tissues have long been overlooked. Chan SunOn and colleagues [10][11][12][13][14][15][16][17][18][19][20][21][22][23] explored the potential role of a group of proteoglycans expressed in the ventral diencephalon and in retina, in the routing and organization of optic fibers at the chiasm. These proteoglycans include sulphated molecules chondroitin sulphate proteoglycans (CS-PGs) and heparan sulfate proteoglycans (HS-PGs), a type of nonsulfated linear glycosaminoglycan hyaluronan (HA), and the cell surface carbohydrate molecule SSEA-1, which is also known as CD15 (leukocyte cluster of differentiation 15) and Lewis-x, a member of the Lewis blood group antigens in humans [24].…”
Section: Guidance Of Retinal Axons In the Optic Chiasm By Proteoglycansmentioning
confidence: 99%